Magnetic shielding paints an accurate and easy-to-visualize portrait of aromaticity. Issue 75 (2nd September 2021) - Karadakov, Peter B.; VanVeller, Brett
Abstract : Computed off-nucleus magnetic shielding isosurfaces and contour plots provide a feature-rich picture of aromaticity and bonding and breathe new life into Clar's aromatic sextet theory. Abstract : Chemists are trained to recognize aromaticity semi-intuitively, using pictures of resonance structures and Frost-Musulin diagrams, or simple electron-counting rules such as Hückel's 4 n + 2/4 n rule. To quantify aromaticity one can use various aromaticity indices, each of which is a number reflecting some experimentally measured or calculated molecular property, or some feature of the molecular wavefunction, which often has no visual interpretation or may not have direct chemical relevance. We show that computed isotropic magnetic shielding isosurfaces and contour plots provide a feature-rich picture of aromaticity and chemical bonding which is both quantitative and easy-to-visualize and interpret. These isosurfaces and contour plots make good chemical sense as at atomic positions they are pinned to the nuclear shieldings which are experimentally measurable through chemical shifts. As examples we discuss the archetypal aromatic and antiaromatic molecules of benzene and square cyclobutadiene, followed by modern visual interpretations of Clar's aromatic sextet theory, the aromaticity of corannulene and heteroaromaticity.